Evidence-Based Homoeopathy: A Case Report of Bilateral Chronic Venous Leg Ulcer Effectively Treated by Individualised Miasmatic Medicines - Ravin, D. Sampaul (Homœopathic Links, 2023)
Venous ulcers can occur when the veins in the legs do not push blood back to the heart. Blood backs up in the veins , building up pressure and accumulation of fluid prevents the nutrients and oxygen from getting to the tissues, resulting in cell death and formation of ulcer. Venous ulcer does interfere with quality of life and induces great deal of discomfort. Conventional medicine mentions chronic venous ulcer as surgical disease. In homoeopathy, this condition is treatable without surgery through individualised miasmatic approach. A successfully treated case of 57 years old male, suffering from bilateral chronic venous leg ulcer, complicated with two miasms is reported here.
Keywords: venous ulcer; surface miasm; sycosis; syphilis; Silicea; Fluoricum acidum